Frequency of and Risk Factors for Depression among Participants in the Swiss HIV Cohort Study (SHCS). - Alexia Anagnostopoulos (PLoS ONE, 2015)
We studied the incidence and prevalence of, and co-factors for depression in the Swiss HIV Cohort Study.Depression-specific items were introduced in 2010 and prospectively collected at semiannual cohort visits. Clinical, laboratory and behavioral co-factors of incident depression among participants free of depression at the first two visits in 2010 or thereafter were analyzed with Poisson regression. Cumulative prevalence of depression at the last visit was analyzed with logistic regression.Among 4,422 participants without a history of psychiatric disorders or depression at baseline, 360 developed depression during 9,348 person-years (PY) of follow-up, resulting in an incidence rate of 3.9 per 100 PY (95% confidence interval (CI) 3.5-4.3). Cumulative prevalence of depression during follow-up was recorded for 1,937/6,756 (28.7%) participants. Incidence and cumulative prevalence were higher in injection drug users (IDU) and women. Older age, preserved work ability and higher physical activity were associated with less depression episodes. Mortality (0.96 per 100 PY, 95% CI 0.83-1.11) based upon 193 deaths over 20,102 PY was higher among male IDU (2.34, 1.78-3.09), female IDU (2.33, 1.59-3.39) and white heterosexual men (1.32, 0.94-1.84) compared to white heterosexual women and homosexual men (0.53, 0.29-0.95; and 0.71, 0.55-0.92). Compared to participants free of depression, mortality was slightly elevated among participants with a history of depression (1.17, 0.94-1.45 vs. 0.86, 0.71-1.03, P = 0.033). Suicides (n = 18) did not differ between HIV transmission groups (P = 0.50), but were more frequent among participants with a prior diagnosis of depression (0.18 per 100 PY, 95%CI 0.10-0.31; vs. 0.04, 0.02-0.10; P = 0.003).Depression is a frequent co-morbidity among HIV-infected persons, and thus an important focus of care.